Design of novel inverse ZrO2/Ni catalysts for CO2 utilization: From CO2 to syn-methane - Li Li; Xueshuang Wu; Jing Yang; Changwei Hu; Patrick Da Costa (Journal of CO2 Utilization, 2025)
The conversion of CO₂ has garnered significant attention due to escalating environmental and resource concerns. The metal-oxide (M-O) interface plays a pivotal role in catalysis, guiding the design of highly active catalysts. Unlike conventional catalysts, inverse catalysts load small inert oxide nanoparticles onto large active metal substrates, emphasizing the importance of the O-M interface. In this study, we synthesized and characterized various ZrO₂/Ni catalysts using a range of techniques, including XRD, BET, H₂-TPR, CO₂-TPD, quasi in-situ XPS, TEM, HRTEM, and in-situ DRIFTS. 70ZrO₂/30Ni catalyst exhibited the highest catalytic performance, attributed to its optimal balance of Ni and ZrO₂, which provided a high ratio of metallic Ni, an increased concentration of oxygen vacancies and more basic sites. These features facilitated efficient CO₂ adsorption and activation, resulting in superior catalytic activity. In-situ DRIFTS experiments revealed that the CO₂ methanation mechanism follows the formate pathway on inverse ZrO₂/Ni catalysts. These findings offer valuable insights into the design and optimization of ZrO₂/Ni catalysts for CO₂ methanation.